Pengembangan Sistem Pengelolaan Risiko Sesuai Requirement As 9100 Di Pt. Dirgantara Indonesia Dengan Pendekatan System Development Life Cycle - Reigi Ahmad Fadilah; Heriyono Lalu; Meldi Rendra (eProceedings of Engineering, 2018)
Abstrak PT. Dirgantara Indonesia merupakan perusahaan kedigantaraan yang berfokus pada desain dan pengembangan pesawat terbang. Untuk menjaga kualitas dan pelayanan PT. Dirgantara Indoensaia tentunya memiliki system untuk mengelola risiko. Sebagai standar kualitas PT. Dirgantara Indonesia menggunakan AS 9100 revisi D. permasalahan yang terjadi pada PT. Dirgantara Indonesia adalah pengelolaan risiko yang analisis risikonya tidak terdokumentasikan sehingga menyebabkan ketidak terukurnya capaian penanganan risiko. Pada penilitian ini akan dilakukan pengembangan system penelolaan risiko berbasis web sesuai dengan requirement AS 9100 revisi D. pada peneitian ini menggunakan metode SDLC (system development life cycle) dengan menentukan streamlining pada proses bisnis eksisting, dan analisis gap antara requirement AS 9100 revisi D klausul 6.1 tentang tindakan mengatasi risiko dan peluang dengan kondisi aktual pengelolaan risiko PT. Dirgantara Indonesia, setelah menemukan masalahnya maka dirancang sebuah system pengelolaan risiko berbasis web yang berisi aplikasi dan standard operational procedure penggunaan aplikasi. Dilakukan blackbox testing untuk rancangan aplikasi dan verifikasi untuk rancangan SOP. Setelah dilakukan blackbox testing dan verifikasi maka dibuat pengembangan system pengelolaan risiko berbasis web PT. Dirgantara Indonesia. Kata kunci : System Development Life Cycle, Pengelolaan Risiko, AS 9100 revisi D, ISO 31000:2009 Abstract To maintain the quality of PT. Dirgantara Indonesia certainly has a system to manage any risks that will occur in each department and also has a international standard for aerospace is AS 9100 revision D to maintain the quality of the company. Risk management system at PT. Dirgantara Indonesia is currently not well documented or no place to keep the assestment risk file that causes the risk handling can not be measured during the implementation of risk mitigation. According to AS 9100 revision D of class 6.1 there needs to be an evaluation of the effectiveness of risktaking measures and opportunities. Therefore, this research focuses on the development of web based risk management system to simplify the process of documentation of risk management with life cycle system development approach. To perform system development there are requirements that are AS 9100 revised requirements D, ISO 31000: 2009. Next step is data processing which analyzes the actual condition with AS 9100 revision requirement D to produce the gap, and also streamlining or simplifying the process on the actual business process of risk management based on gap analysis which has been analyzed previously. The results of the design that has been obtained then made improvements so as to get business process proposals web-based risk management, with web design using data flow diagrams, entities relationship diagram, and user interfaces to facilitate the appearance of risk management web. This research resulted in a new risk management system that incorporates proposed business processes and risk management web applications. Then from the design of the risk management system will be documented in the form of SOP. Kata kunci : System Development Life Cycle, Risk Management, AS 9100 revision D, ISO 31000:2009